Urban biodiversity of pseudoscorpions (Arachnida: Pseudoscorpiones) in the conditions of Central Europe - Christophoryová, Jana; Rusinko, Adam; Purkart, Adrián; Vičanová, Lucia (Zootaxa, 2025)
Like other arthropod taxa, pseudoscorpions (Arachnida: Pseudoscorpiones) face challenges in dynamically evolving urban ecosystems. These small predators must find suitable breeding habitats and migrate within fragmented environments. This is compounded by the limitations of their body size and their association with specific ecological conditions. The present study uncovers the pseudoscorpion diversity in Bratislava, the capital of Slovakia. In 1882–2022, pseudoscorpions were collected from 191 sampling sites using various methods. As a result, 5260 pseudoscorpions belonging to 26 species and six families were recorded. Thanks to the newly collected data, two families (Cheiridiidae and Withiidae) and four species, Chthonius ischnocheles (Hermann, 1804), Apocheiridium ferum (Simon, 1898), Mesochelifer ressli Mahnert, 1981 and Withius hispanus (L. Koch, 1873), were documented for the first time in Bratislava. The most abundant species were Neobisium carcinoides (Hermann, 1804) and Lamprochernes chyzeri (Tömösváry, 1882), while the least abundant species were Chthonius ischnocheles and Dendrochernes cyrneus (L. Koch, 1873). Pseudoscorpions were collected from different types of (micro-)habitats, the highest species diversity was found in a substrate (soil, leaf litter) and composts. Only the species Allochernes peregrinus Lohmander, 1939, and Lamprochernes chyzeri were recorded as phoronts attached to Diptera hosts, and only the species Chelifer cancroides (Linnaeus, 1758) occurred in the synanthropic environment including building interiors. Data on European distribution, habitat preferences, and taxonomic considerations are reported. Pseudoscorpion fauna from Bratislava is compared with that of other neighbouring capitals.